Fe/Mn nanoparticles encapsulated in nitrogen-doped carbon nanotubes as a peroxymonosulfate activator for acetamiprid degradation. Issue 6 (25th April 2019) - Duan, Pijun; Ma, Tengfei; Yue, Yue; Li, Yanwei; Zhang, Xue; Shang, Yanan; Gao, Baoyu; Zhang, Qingzhu; Yue, Qinyan; Xu, Xing
Abstract : Bimetallic Fe/Mn nanoparticles and N-doped carbon nanotubes in FeMn@NCNT synergistically activate peroxymonosulfate to form SO4 ˙ −, ˙OH, O2 ˙ − and 1 O2 for decomposing acetamiprid. Abstract : N-Doped carbon nanotubes encapsulating bimetallic Fe/Mn nanoparticles (FeMn@NCNTs) were fabricated after a one-step pyrolysis and were used as the catalyst for peroxymonosulfate activation to degrade acetamiprid. The FeMn@NCNTs showed uniform nanotubes with rich N doping and the encapsulated FeMn nanoparticles were doubly protected by both NCNTs and a clingy graphitic structure. The results indicated that the confined FeMn nanoparticles were designated as Fe2.7 Mn0.3 C according to the XRD pattern and elemental composition. Radical quenching indicated that SO4 ˙ − and ˙OH were the dominant radicals in the FeMn@NCNTs/PMS system. The indispensable roles of both radical pathways of O2 ˙ − and non-radical 1 O2 in the superior catalytic performance were also confirmed. As a result, both the embedded FeMn nanoparticles and NCNTs in FeMn@NCNTs contributed to the acetamiprid degradation with multiple degradation mechanisms. XPS results confirmed the formation of redox cycles between the multiple valence states of Mn and Fe, which ensured the superior catalytic activity of FeMn@NCNTs for PMS activation. In addition, only a small decrease in the catalytic performance from 99.5% to 90% was observed after four cycles. The catalytic activity of used FeMn@NCNTs was mostly recovered after heat regeneration (350 °C), which exhibited the excellent stability and reusability of the FeMn@NCNTs.